Deepsea mining, transfer of technology and the new international economic order in the context of South - Asia - Rev. Fr. Dias, K.J.F.N. (My University, 1994)
The underlying theme of the thesis is justice. Justice links up different aspects in the manner shown below. The first part of the thesis attempts to establish normative jurisprudential criteria of international social justice. Thomistic on justice and law form forms the basis of this inquiry...